Teacher Stress and Free Time as a Space for Dealing with Stress - Jukić, Renata; Ham, Emanuela (Acta Paedagogica Vilnensia, 2024)
The aim of this paper is to examine teachers’ stress and free time as a space for coping with stress. When teachers experience negative emotions such as anxiety or frustration due to some form of their work, this is referred to as teacher stress. Research shows that teachers’ reported stress levels continue to increase. Free time is a space where teachers can use external support and personal resources to mitigate the negative effects of teacher stress. From a pedagogical point of view, it is therefore important to design quality free time to prevent and reduce teacher stress and improve teacher well-being.
Keywords: well-being; professional stress; workload; job satisfaction